Legacy of violence: lynch mobs and executions in Minnesota - Bessler, John D. (University of Minnesota Press, 2003)
Lynch mobs and public hangings -- On Lincoln's orders : Mankato's mass hanging -- The execution of Ann Bilansky -- The gallows reconsidered : executions versus life sentences -- The "midnight assassination law" -- The botched hanging of William Williams -- The abolition of capital punishment -- A travesty of justice : the Duluth lynchings.